TEACHERS’ PERSPECTIVES ON MULTILINGUAL EDUCATION IN EARLY CHILDHOOD: A CASE STUDY OF TADIKA MUJAHEDEEN KINDERGARTEN, SOUTHERN THAILAND - Munawarah Munawarah; Faizatul Husna; Rena Juliana; Chantana Muhammad (STKIP Persada Khatulistiwa Sintang, 2026)
Southern Thailand has a rich plurilingual background in the context of early childhood education. At home, children generally speak Patani Malay, while Thai serves as the national language and medium of instruction, Arabic is used in religious activities, and English is taught as a foreign language. This study aims to explore educators' perspectives on plurilingual education at Tadika Mujahedeen, as well as to identify various challenges and opportunities that arise in daily learning practices.The research design employed was descriptive qualitative, involving three educators and one parent as participants, who were selected through purposive sampling. Data collection was conducted through semi-structured interviews and analyzed thematically to examine language use, learning approaches, and their impact on child development. Research findings show that Thai serves as the primary language in the learning process, whereas Patani Malay, English, and Arabic are introduced contextually through child-centered activities such as singing, storytelling, and playing. Educators report challenges related to the linguistic diversity of learners and their limited proficiency in certain languages. Nevertheless, adaptive strategies and cooperation with parents have proven effective in supporting plurilingual learning.Plurilingual education is seen as capable of increasing children's confidence, communication skills, and positive attitudes toward language learning. Overall, this study reveals how plurilingual practices are naturally integrated into daily classroom interactions in Islamic-based early childhood education settings in Southern Thailand.